Immigration and Economic Growth in the OECD Countries 1986-2006 - Ekrame Boubtane; Jean-Christophe Dumont; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper offers a reappraisal of the impact of migration on economic growth for 22 OECD countries between 1986-2006 and relies on a unique data set we compiled that allows us to distinguish net migration of the native- and foreign-born populations by skill level. Specifically, after introducing migration in an augmented Solow-Swan model, we estimate a dynamic panel model using a system of generalized method of moments (SYS-GMM) to address the risk of endogeneity bias in the migration variables. Two important findings emerge from our analysis. First, there exists a positive impact of migrants' human capital on GDP per capita, and second, a permanent increase in migration ows has a positive effect on productivity growth. However, the growth impact of immigration is small even in countries that have highly selective migration policies.
Keywords: C23; F22; J24; J61; O41; O47; 330; immigration; growth; human capital; generalized methods of moments